1996
DOI: 10.1021/jp962227f
|View full text |Cite
|
Sign up to set email alerts
|

Subpicosecond Interfacial Charge Separation in Dye-Sensitized Nanocrystalline Titanium Dioxide Films

Abstract: We have employed subpicosecond transient absorption spectroscopy to study the rate of electron injection following optical excitation of the ruthenium dye Ru II (2,2′-bipyridyl-4,4′-dicarboxylate) 2 (NCS) 2 (1) adsorbed onto the surface of nanocrystalline titanium dioxide (TiO 2 ) films. This sensitizer dye is of particular interest as it is the most efficient sensitizer dye reported to date and is receiving considerable attention for applications in photoelectrochemical solar energy conversion. Transient data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

67
1,064
6
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 847 publications
(1,138 citation statements)
references
References 25 publications
67
1,064
6
1
Order By: Relevance
“…Charge injection in zirconia is not thermodynamically feasible, and, as a result, the ground-state absorption of the dye is promptly recovered by deactivation of the excited state (eq 3), whose lifetime on the oxide surface is estimated to be τ 1/2 = 15 ns. 18,19 From the very long lifetime of the bleaching signal observed for the dye adsorbed on SrTiO 3 , it is thus concluded that charge injection (eq 2) does indeed occur quantitatively (Φ inj > 0.8) into this material. The slow recovery of the initial absorbance of the adsorbed dye is attributed to the back electron transfer reaction (eq 5).…”
Section: Resultsmentioning
confidence: 98%
“…Charge injection in zirconia is not thermodynamically feasible, and, as a result, the ground-state absorption of the dye is promptly recovered by deactivation of the excited state (eq 3), whose lifetime on the oxide surface is estimated to be τ 1/2 = 15 ns. 18,19 From the very long lifetime of the bleaching signal observed for the dye adsorbed on SrTiO 3 , it is thus concluded that charge injection (eq 2) does indeed occur quantitatively (Φ inj > 0.8) into this material. The slow recovery of the initial absorbance of the adsorbed dye is attributed to the back electron transfer reaction (eq 5).…”
Section: Resultsmentioning
confidence: 98%
“…Under all pH conditions, negligible oxidized peak amplitude was observed at <200 fs, indicating a lack of instantaneous injection component that was observed for RuN3 and derivatives on TiO 2 . 36,[63][64][65][66][67][68][69] This has been attributed to the insertion of a CH 2 spacer between the bipyridine and the anchoring group, which reduces its electronic coupling with TiO 2 , slowing down the electron injection rate. 40 At pH 0, the excited-state CO stretch band disappears completely by ∼50 ps, with a concurrent appearance of the oxidized-state band.…”
Section: Ph Dependence Of Photophysicsmentioning
confidence: 99%
“…[7][8][9][10][11] This feature is associated with the population dynamics of different metalto-ligand charge-transfer (MLCT) states of the dye complex. Following excitation at the maximum of the absorption band (typically at a wavelength of 530 nm), the dye is initially prepared in the singlet 1 MLCT state.…”
Section: Introductionmentioning
confidence: 99%